SADAR PAJAK SEJAK DINI DALAM PENDIDIKAN - Reva Maria Valianti; Emma Lilianti; Hendry Saladin; Juni Darwin (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
The largest source of government funding to finance development is obtained from taxation, the mechanism of which is coercive in accordance with Indonesian law. The low awareness of taxpayers to obey taxes is the biggest problem faced by the Directorate General of Tax (DGT). The desire to change change the mindset of the public to be aware of taxation with early education requires systematic technical, one of which is through inclusion in learning materials and student activities. The implementation method with the extension method, through the preparation phase, the implementation stage and the results phase. Based on the observations of the PKM team when the activity took place, the students' interest in the material provided was very high. The enthusiasm of the participants and the average active participant in listening to the extension material. This observation was shown with high student curiosity so many questions were asked to the speakers. The liveliness of the resource persons who also asked questions to students as far as they were familiar with taxation was shown by the results of the post-test showing a response of 99% of students stating they began to understand obligations as taxpayers